A Study on Photostability of Ethyl Glucuronide in Hair Irradiated under Artificial Sunlight. Issue 1 (22nd January 2019) - Miolo, Giorgia; Stocchero, Giulia; Vogliardi, Susanna; Menilli, Luca; Scrivano, Salvatore; Montisci, Massimo; Favretto, Donata
Abstract: Drugs incorporated into hair are exposed to the environment, and cosmetic and chemical treatments, with possible decreases in their content. Knowledge concerning the effect of sunlight on drug content in hair can be helpful to forensic toxicologists, in particular, when investigating drug concentrations above or below pre-determined cut-offs. Twenty-eight authentic positive hair samples were selected which had previously tested positive for ethyl glucuronide (EtG). Washed hair were divided into two identical tufts, with the former exposed at 13, 219 J/cm 2 (300–800 nm spectrum of irradiance) for 48 h in a solar simulator, and the latter kept in the dark. Hair samples were extracted and analyzed by ultra performance liquid chromatography–tandem mass spectrometry. The percentage of photodegradation was calculated for EtG. In parallel, photodegradation processes of standard molecule dissolved in aqueous and organic solutions were studied. In 28 hair samples, positive for the targeted analyte, exposure to artificial sunlight induced an appreciable increase in EtG concentrations. The concentration range in the non-irradiated hair samples was 6.0–772.0 pg/mg, and 64.3% of samples exhibited an increase in post-irradiation samples, ranging from 7% to 255%. In seven cases, a decrease was observed ranging from −5.0% to −36.0%. Thus, either a decrease or an increase of EtG may be observed post-irradiation, depending on hair color and/or hair thickness. Because the denaturation status of hair fibers and the thickness of hair before irradiation could play a role, a scanning electron microscope study should be envisaged.